Interfaces: Explorations in Logic, Language and Computation ESSLLI 2008 and ESSLLI 2009 Student Sessions. Selected Papers - Icard, Thomas; Muskens, Reinhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The European Summer School in Logic, Language and Information (ESSLLI) takes place every year, each time at a di?erent location in Europe. With its focus on the largeinterdisciplinaryareawhere linguistics,logic andcomputation converge, it has become very popular since it started in 1989, attracting large crowds of students. ESSLLI is where everyone in the ?eld meets, teaches, takes courses, gives talks, dances all night, and generally has a good time. One of the enjoyable features of the School is its recurring Student Session, organized by students along the lines of a conference. The speakers are students too, who are eager to get a chance to present their work. They face sti? com- tition to get their talks accepted, as the number of papers that is sent in each year is high and acceptance rates low. In my experience many of the selected talks contain fresh and surprising insights and are a pleasure to attend. But the reader may judge the quality of the Student Session for himself, as this volume contains a selection of papers from its 2008 and 2009 installments, the ?rstheld in Hamburg,the secondin Bordeaux.The book is divided into four parts.
Semantics and Pragmatics -- Can DP Be a Scope Island? -- Semantic Meaning and Pragmatic Inference in Non-cooperative Conversation -- What Makes a Knight? -- The Algebraic Structure of Amounts: Evidence from Comparatives -- Mathematical Linguistics -- Extraction in the Lambek-Grishin Calculus -- Formal Parameters of Phonology -- Applied Computational Linguistics -- Variable Selection in Logistic Regression: The British English Dative Alternation -- A Salience-Driven Approach to Speech Recognition for Human-Robot Interaction -- Language Technologies for Instructional Resources in Bulgarian -- Logic and Computation -- Description Logics for Relative Terminologies -- Cdiprover3: A Tool for Proving Derivational Complexities of Term Rewriting Systems -- POP* and Semantic Labeling Using SAT.
Keywords: Computer science; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Electronic books